Perilaku Konsumsi Generasi Z terhadap Minuman Tradisional Bir Pletok Betawi di Universitas Budi Luhur - Anindya Putri Pradiptha; Jasmine Qur’ani; Tina Selviana (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to find out how Generation Z behaves towards Traditional Drinks, where the current generation has a modern lifestyle but is less aware of Traditional Drinks which are rich in history and culture. Current developments by Generation Z can have a negative effect in forgetting the history and cultural knowledge of these drinks. Therefore, in this research it can be seen how behavior and lifestyle can unite cultures in their lives. The method used in this research was to distribute questionnaires to students of the Tourism Study Program at Budi Luhur University, then provide samples of Pletok Betawi Beer as their opinion regarding whether the drink was well received, and knowing the existing culture and history. Then, the collected data will be processed using SPSS version 29 to identify patterns and relationships between Generation Z behavior and lifestyle Keywords: Betawi Pletok Beer, Consumer Behavior, Generation Z, Lifestyle